DEVELOPMENT OF WEBSITE-BASED LEARNING MEDIA ON THE PRACTICE OF PANCASILA ON STUDENT LEARNING MOTIVATION - Diana Puspita Dewi; Ani Nur Aeni; Rana Gustian Nugraha (Jurnal Cakrawala Pendas, 2023)
The ethical awareness had been fading in the Pancasila culture, make some consecuencses that growing negative influence on the younger generation to come. Moreover, the existence of moral degradation and the influence of the so call the era of disruption has  potential to acquire ideology’s that  contrary to Pancasila. However, the interest of fourth-grade students in learning civics education is still lacking. The results of the initial survey stated that students felt sleepy when learning civics education, in area of the learning media has lacked innovation, namely only using thematic books, tended to be teacher-centered, and students lacked active participation. So that this study developed a website-based media on the practice of Pancasila for motivation to learn Civics Education. This study will use the Research and Development method with the ADDIE model. Data processing in this research is descriptive quantitative. The results obtained from this study were that media and material feasibility tests obtained an average of 94% and 87.4% with very feasible criteria. Product use tests were carried out by small groups and large groups with the results of the respondents indicating a positive attitude towards the media. Then, the motivation to learn civics education obtains an average of 84% and is classified as a very good criteria. So it can be concluded that the development of website-based media can have an influence on interest in learning civics education. With the motivation towards Civics education, students can apply the values ​​contained therein well in the future. Kesadaran etika yang telah memudar terhadap budaya pancasila, menimbulkan beberapa konsekuensi yaitu tumbuhnya pengaruh negatif terhadap generasi muda yang akan datang. Apalagi adanya degradasi moral dan pengaruh era disrupsi berpotensi memperoleh ideologi yang bertentangan dengan Pancasila. Namun, minat peserta didik kelas IV dalam pembelajaran Pendidikan Kewarganegaraan masih kurang. Hasil survey awal menyatakan bahwa peserta didik merasa ngantuk ketika belajar Pendidikan Kewarganegaraan, media pembelajaran kurang inovasi yaitu hanya menggunakan buku tematik, cenderung pembelajaran berpusat pada guru, dan partisipasi aktif peserta didik kurang. Sehingga dalam penelitian ini mengembangkan media berbasis website materi pengamalan Pancasila untuk motivasi belajar Pendidikan Kewarganegaraan. Dalam penelitian ini menggunakan metode Reseacrh and Development (R&D) dengan model ADDIE. Pengolahan data dalam penelitian ini secara kuantitatif deskripstif. Hasil yang diperoleh dari penelitian ini bahwa uji kelayakan media dan materi memperoleh rata-rata 94% dan 87,4% dengan kriteria sangat layak. Uji penggunaan produk dilakukan oleh kelompok kecil dan kelompok besar dengan hasil responden diindikasikan positif terhadap media. Kemudian, motivasi belajar pendidikan kewarganegaraan setelah menggunakan media memperoleh rata-rata sebesar 84% dan tergolong kriteria sangat baik. Sehingga dapat disimpulkan bahwa pengembangan media berbasis website dapat memberikan pengaruh terhadap minat belajar pendidikan kewarganegaraan dan berharap dapat meningkatkan motivasi dan hasil belajar peserta didik untuk kedepannya. Dengan adanya motivasi terhadap pendidikan kewarganegaraan, peserta didik dapat menerapkan nilai-nilai yang terkandung di dalamnya dengan baik di masa depan.